Urban society - Levine, Myron A. (New York : ill., 2010)
Offers access to a range of articles from some of the most respected magazines, newspapers, and journals. This title features common organizational features useful in the classroom: a general introduction; an annotated table of contents; a topic guide; an annotated listing of selected World Wide Web sites; and a brief overview for each section.
1. Urban growth, decline, and renaissance -- 2. Gentrification, globalization and the city -- 3. Competitive pressures and economic development -- 4. Citizen participation -- 5. School choice and school reform -- 6. Policing and crime -- 7. A suburban nation: suburban growth, diversity, and the possibilities of a "new urbanism" and a "new regionalism" -- 8. Toward sustainable cities and suburbs -- 9. The future of cities and suburbs: the United States and the world
Includes bibliographical references
Keywords: Social psychology; Sociology; Sociology, Urban; Urbanization